La mise en scène de la créativité dans l’œuvre de Michel Gondry : récursivité, boucle étrange et cognition - Camille Périssé (Mise au Point)
There are many representations of creativity in Michel Gondry's cinema. In fact, in a more or less explicit way, the director regularly stages characters who imagine objects or original solutions to understand their environment. As we will detail, the mise en abyme of creativity generally takes as a pretext phenomena that everyone experiences and that belong to the domain of cognition: memory in Eternal Sunshine of the Spotless Mind, dreams in Science dreams or collective intelligence in Be nice, rewind. This article hypothesizes that Michel Gondry's desire to trace the thread of his creative thought to its cognitive origin causes a recurrence of the mise en abyme and the loop in his cinema.